Deficits in the Mitochondrial Enzyme α-Ketoglutarate Dehydrogenase Lead to Alzheimer’s Disease-like Calcium Dysregulation - Gibson, Gary E. (2011)
Understanding the molecular sequence of events that culminate in multiple abnormalities in brains from patients that died with Alzheimer’s Disease (AD) will help to reveal the mechanisms of the disease and identify upstream events as therapeutic targets. The activity of the mitochondrial α-ketoglutarate dehydrogenase complex (KGDHC) in homogenates from autopsy brain declines with AD. Experimental reductions in KGDHC in mouse models of AD promote plaque and tangle formation, the hallmark pathologies of AD. We hypothesize that deficits in KGDHC also lead to the abnormalities in endoplasmic reticulum (ER) calcium stores and cytosolic calcium following K(+) -depolarization that occur in cells from AD patients and transgenic models of AD. The activity of the mitochondrial enzyme KGDHC was diminished acutely (minutes), long term (days) or chronically (weeks). Acute inhibition of KGDHC produced effects on calcium opposite to those in AD, while the chronic or long term inhibition of KGDHC mimicked the AD-related changes in calcium. Divergent changes in proteins released from the mitochondria that effect ER calcium channels may underlie the selective cellular consequences of acute versus longer term inhibition of KGDHC. The results suggest that the mitochondrial abnormalities in AD can be upstream of those in calcium.